ADVANCES IN TOTAL SYNTHESIS OF ALTERNARIC ACID: AN ANTI-FUNGAL AND PHYTOTOXIC NATURAL PRODUCT - Ahmad, Sajjad; Yousaf, Muhammad; Fawad Zahoor, Ameer; Ahmad, Matloob; khan, Zulfiqar Ali; Rashid, Muhammad Arslan (Journal of the Chilean Chemical Society, 2017)
Alternaric acid is characterized as 1,4-diene, possessing (E)-1,2-disubstituted alkene known for nanomolar phytotoxic and antifungal activities. This article highlights the major synthetic approaches attempted towards the total synthesis of alternaric acid reported by three groups (Ichihara & coworkers, Trost & coworkers and Johnson and Slade) which involved novel pathways for the rapid construction of this functionalized natural molecule.